Enhancing drone education in Malaysia: STEM and TVET framework perspective - Mohd Noh, Mohd Hafiz; Mohd Abbas, Norliana; Abdul Hamid, Ahmad Hussein; Mohd Nor, Mohd Fitri Reza (Penerbit UiTM (UiTM Press), 2026)
The integration of drone technology into education is increasingly recognised as a means to enhance Science, Technology, Engineering, and Mathematics (STEM) learning and Technical and Vocational Education and Training (TVET). Despite its potential, Malaysia faces challenges in fully integrating drones into the education system, including a lack of structured curricula, insufficient training for educators, and regulatory constraints. This study explores the integration of STEM and TVET principles into drone education and training in Malaysia, aiming to bridge the gap between technological advancements and workforce readiness. The primary objectives of this study are to analyse the current state of drone education in Malaysia, identify key implementation challenges, and develop a structured framework for integrating drone education into STEM and TVET programs. A mixed-methods research approach was employed, combining quantitative assessments, qualitative evaluations, pre- and post-assessment, and workshop based training to measure participants’ knowledge improvement and engagement. Initial findings reveal that structured drone training programs significantly enhance students’ technical competencies, safety awareness, and career preparedness, but are not very effective from a regulatory compliance perspective. The Reusable Learning Object (RLO) approach has been used for the Safety and Regulations module, and it has significantly improved candidates’ understanding.